STRATEGIES OF LAMPUNG MUSLIM COMMUNITY TO FACE TRANSNATIONAL GLOBALIZATION - Aris Munandar; Ariska, Ayu (Madura State Islamic Institute (Institut Agama Islam Negeri (IAIN) Madura), 2024)
Abstract This research aims to identify and analyze the strategies of Muslim communities in Lampung in maintaining their cultural and religious identities amid the influence of transnational globalization, especially with the presence of imported ideologies such as Wahhabi-Salafi fundamentalism and secular liberalism, as well as transnational Islamic movements such as Hizbut Tahrir Indonesia (HTI). This research also seeks to understand how the interaction between globalization, local identity and religion affects religious practices and social structures in Lampung, as well as evaluate the policies and measures taken by the local government in dealing with the influence of these transnational ideologies. This research uses a qualitative approach with a case study method to explore the strategies of Lampung Muslim communities in dealing with transnational globalization and the influence of movements such as HTI. Data was collected through in-depth interviews with community leaders, religious leaders, and community members, as well as participatory observation at various religious events and activities. The research findings show that Lampung Muslim communities adopt various strategies to maintain their cultural and religious identity amidst globalization. These include preserving local culture through arts and customs programs, developing the local economy by utilizing digital technology, and strengthening religious education to ensure Islamic values are passed on to the next generation. Despite HTI's success in garnering support through proselytizing and street demonstrations, the government's decisive action in dissolving HTI reflects efforts to maintain national stability and defend the ideology of Pancasila. Abstract Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis strategi masyarakat Muslim di Lampung dalam mempertahankan identitas budaya dan agama mereka di tengah pengaruh globalisasi transnasional, terutama dengan adanya ideologi-ideologi impor seperti fundamentalisme Wahhabi-Salafi dan liberalisme sekuler, serta gerakan Islam transnasional seperti Hizbut Tahrir Indonesia (HTI). Penelitian ini juga berusaha memahami bagaimana interaksi antara globalisasi, identitas lokal, dan agama mempengaruhi praktik keagamaan dan struktur sosial di Lampung, serta mengevaluasi kebijakan dan langkah-langkah yang diambil oleh pemerintah setempat dalam menangani pengaruh ideologi transnasional ini. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus untuk mengeksplorasi strategi masyarakat Muslim Lampung dalam menghadapi globalisasi transnasional dan pengaruh gerakan seperti HTI. Data dikumpulkan melalui wawancara mendalam dengan tokoh masyarakat, pemimpin agama, dan anggota komunitas, serta observasi partisipatif di berbagai acara dan kegiatan keagamaan. Temuan penelitian menunjukkan bahwa masyarakat Muslim Lampung mengadopsi berbagai strategi untuk mempertahankan identitas budaya dan agama mereka di tengah arus globalisasi. Upaya tersebut meliputi pelestarian budaya lokal melalui program kesenian dan adat istiadat, pengembangan ekonomi lokal dengan memanfaatkan teknologi digital, serta penguatan pendidikan agama untuk memastikan nilai-nilai Islam diwariskan kepada generasi berikutnya. Meskipun HTI berhasil menggalang dukungan melalui dakwah dan demonstrasi jalanan, tindakan tegas pemerintah dalam membubarkan HTI mencerminkan upaya untuk menjaga stabilitas nasional dan mempertahankan ideologi Pancasila.